Uncertainty Revisited: People and Information in a World of Unknowns - Kamal, Ahmad M.; Burkell, Jacquelyn (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
Psychological uncertainty is established in LIS models, but epistemic and aleatory uncertainties remain absent. We critically review the concept of uncertainty in LIS and beyond. Presenting a new framework on uncertainty for LIS, we suggest new approaches to more fully address the uncertain world we and our subjects inhabit. L’incertitude psychologique est un modèle établi en science de l’information, mais l’incertitude épistémique et l’incertitude aléatoire demeurent absentes. La communication propose une revue critique du concept d’incertitude en science de l’information et dans d’autres disciplines. En présentant un nouveau cadre conceptuel relatif à l’incertitude en science de l’information, nous suggérons de nouvelles approches pour mieux aborder le monde incertain dans lequel nous et nos sujets habitons. ***Full paper in the Canadian Journal of Information and Library Science***